2018
DOI: 10.1002/pc.24954
|View full text |Cite
|
Sign up to set email alerts
|

Thermo‐mechanical properties of glass fiber and functionalized multi‐walled carbon nanotubes filled polyester composites

Abstract: Glass fiber (GF) and hydroxyl‐functionalized multi‐walled carbon nanotubes (MWCNTs)‐reinforced polyester‐based composites were prepared by solution casting technique. Unsaturated polyester (UPE) was mixed separately with a fixed amount (0.5 wt%) of hydroxyl‐functionalized MWCNTs and GF (5.0 wt%). Multi‐walled carbon nanotubes (MWCNTs) were functionalized with hydroxyl functional group (OH) prior to the fabrication of the composites. The structural properties were evaluated by Fourier transform infrared spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…The storage moduli at 25 C increased by 2.5 to 43.1% with different types of MWCNTs additions. In a study conducted by Islam et al [35], a 14% increase was observed in the storage modulus value with the addition of MWCNT-OH to the polyester-based composite material, while the increase in the storage modulus values varied between 20-40% in the studies conducted with MWCNT added epoxy resin-based composites [3,18]. This high increment achieved in this study can be related to the good dispersion of nanoparticles in the matrix.…”
Section: Storage Modulussupporting
confidence: 51%
See 2 more Smart Citations
“…The storage moduli at 25 C increased by 2.5 to 43.1% with different types of MWCNTs additions. In a study conducted by Islam et al [35], a 14% increase was observed in the storage modulus value with the addition of MWCNT-OH to the polyester-based composite material, while the increase in the storage modulus values varied between 20-40% in the studies conducted with MWCNT added epoxy resin-based composites [3,18]. This high increment achieved in this study can be related to the good dispersion of nanoparticles in the matrix.…”
Section: Storage Modulussupporting
confidence: 51%
“…With the addition of different MWCNT types, a decrease in tan delta value between 12.5% and 20% was observed. In the study carried out by Islam et al [35], it was observed that the decrease in tan delta value was around 25% where MWCNT-OH added polyester resin was utilized as a matrix system. Moreover, it is known that between –OH functional group of MWCNT-OH and >C = O functional group of unsaturated polyester resin, a hydrogen bond is created, while π-π interactions between pristine MWCNT and unsaturated polyester resin is formed owing to the characteristics of carbon nanostructures [33].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of microcracks at the surface reduces the flexural properties of the composites. [ 38‐39 ]…”
Section: Resultsmentioning
confidence: 99%
“…The formation of microcracks at the surface reduces the flexural properties of the composites. [38][39] Table 1 shows the IS of the NE and EFS composites before and after degradation. It was found that the IS of the NE and EFS composites before degradation were 5.9 and 2.9 kJ/m 2 , respectively.…”
Section: Mechanical Propertiesmentioning
confidence: 99%